The effects of nutritional level and body condition score on cytokines in seminal plasma of beef bulls - Harrison, Taylor D.; Chaney, Elizabeth M.; Brandt, Kiernan J.; Ault-Seay, Taylor B.; Payton, Rebecca R.; Schneider, Liesel G.; Strickland, Lew G.; Schrick, F. Neal; McLean, Kyle J. (Frontiers in Animal Science, 2023)
Introduction High quality semen is essential for reproductive efficiency. Nutrition and environmental factors impact the ejaculate components, like cytokines, that are essential for pregnancy establishment. We hypothesized that differing nutritional periods and body condition scores would affect seminal plasma cytokine concentrations of bulls. Methods Mature Angus bulls (n=11) were individually housed and randomly assigned to either over-fed (n=5) or restricted (n=6) treatment pathways. Bulls were fed different volumes of a single ration creating 8 individual treatment periods. Body weight and body condition scores were taken every 14 d to manage intake volumes. Ejaculates were collected every 84 d to determine seminal plasma cytokine profiles. A complete randomized design was used to evaluate seminal plasma cytokines after each nutritional treatment. Initial cytokine concentrations and volume of the ejaculate were included as covariates. Results All cytokines returned to initial concentrations following maintenance treatments at an ideal body condition score of 6. Nutritional treatments affected (P ≤ 0.05) IFN-γ, IL-8, MIP-1α, MIP-1β, TNF-α, IL-1β, and VEGF-A. However, TNF-α, IFN-γ, and MIP-1α had the greatest impact on cytokine profile. Discussion Nutritional levels and adiposity altered seminal plasma cytokine concentrations which could potentially impact the inflammatory balance of the uterus and the immune responses necessary for pregnancy establishment.